Asymmetric growth-limiting development of the female conceptus - Estrella, Consuelo Amor S.; Gatford, Kathryn L.; Xiang, Ruidong; Javadmanesh, Ali; Ghanipoor-Samami, Mani; Nattrass, Greg S.; Shuaib, Entesar; McAllister, Milton M.; Beckman, Ian; Thomsen, Dana A.; Clifton, Vicki L.; Owens, Julie A.; et al. (Frontiers in Endocrinology, 2024)
Sex differences in prenatal growth may contribute to sex-dependent programming effects on postnatal phenotype. For the first time we integrate phenotypic, histomorphological, clinico-chemical, endocrine and gene expression analyses in a single species, the bovine, to demonstrate that by mid-gestation, before the onset of accelerated growth, the female conceptus displays asymmetric lower growth compared to males. Female fetuses were smaller with lower ponderal index and organ weights than males. However, their brain:body weight, brain:liver weight and heart:body weight ratios were higher than in males, indicating brain and heart 'sparing'. The female placenta weighed less and had lower volumes of trophoblast and fetal connective tissue than the male placenta. Female umbilical cord vessel diameters were smaller, and female-specific relationships of body weight and brain:liver weight ratios with cord vessel diameters indicated that the umbilico-placental vascular system creates a growth limiting environment where blood flow is redistributed to protect brain and heart growth. Clinico-chemical indicators of liver perfusion support this female-specific growth-limiting phenotype, while lower insulin-like growth factor 2 (IGF2) gene expression in brain and heart, and lower circulating IGF2, implicate female-specific modulation of key endocrine mediators by nutrient supply. This mode of female development may increase resilience to environmental perturbations in utero and contribute to sex-bias in programming outcomes including susceptibility to non-communicable diseases.